2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591012
|View full text |Cite
|
Sign up to set email alerts
|

Idle state classification using spiking activity and local field potentials in a brain computer interface

Abstract: Previous studies of intracortical brain-computer interfaces (BCIs) have often focused on or compared the use of spiking activity and local field potentials (LFPs) for decoding kinematic movement parameters. Conversely, using these signals to detect the initial intention to use a neuroprosthetic device or not has remained a relatively understudied problem. In this study, we examined the relative performance of spiking activity and LFP signals in detecting discrete state changes in attention regarding a user's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…As a result, the nearby neurons would have a dampened ability to generate action potentials that can be recorded by the electrode. Despite these intrinsic network changes, a multitude of BCI studies, as well as our studies in rodent visual cortex, indicate that chronically implanted intracortical electrodes are still capable of recording and extracting functional information 79,39,41,55,111115 . Nevertheless, large variability in device performance is well documented 79,29,93,116 .…”
Section: Discussionmentioning
confidence: 91%
“…As a result, the nearby neurons would have a dampened ability to generate action potentials that can be recorded by the electrode. Despite these intrinsic network changes, a multitude of BCI studies, as well as our studies in rodent visual cortex, indicate that chronically implanted intracortical electrodes are still capable of recording and extracting functional information 79,39,41,55,111115 . Nevertheless, large variability in device performance is well documented 79,29,93,116 .…”
Section: Discussionmentioning
confidence: 91%
“…When algorithms for updating BCI decoders consider the change in movement direction for corrective movements, it is assumed the intended path is updated continuously (Gilja et al, 2012; Shanechi et al, 2016). Experiments have suggested that BCI control can be improved with two states: active control and rest (Kim et al, 2011; Williams et al, 2013, 2016; Sachs et al, 2016). The ability to predict the phase of a movement—like CIφ presented here—might further allow for much better prediction of when the subject intends to move, contact the target, and make a corrective movement.…”
Section: Discussionmentioning
confidence: 99%
“…When algorithms for updating BCI decoders consider the change in movement direction for corrective movements, it typically has been assumed the intended path is updated continuously (Gilja et al, 2012; Shanechi et al, 2016). Experiments have suggested that BCI control can be improved with two states: active control and rest (Kim et al, 2011; Williams et al, 2013, 2016; Sachs et al, 2016). Our results suggest that computing the phase of cyclic, condition-independent neural activity with CIφ (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCI are systems that translate brain signals into commands to control external devices [1] . Brain signals can be acquired by means of different 207 techniques as magnetoencephalography (MEG) [38] , near-infrared spectroscopy (NIRS) [39] , electrocorticography (ECoG) [40] , local field potentials (LFP) recordings [41] , electroencephalography (EEG) [42] , among others. MEG has the best compromise between time and spatial resolution, however, it also the most complex acquisition modality for BCI and the least available for practical applications.…”
Section: Brain-computer Interfacesmentioning
confidence: 99%